Educational intervention to decrease stigmatizing attitudes of undergraduate nurses towards people with mental illness. (7th March 2017) - Bingham, Helen; O'Brien, Anthony John
Abstract: Health professionals can hold stigmatizing views about people with mental illness. In addition to being discriminatory, these beliefs cause anxiety that can affect learning in the clinical environment. A review of an undergraduate nursing curriculum introduced the Modern Apprenticeship curriculum model and provided an opportunity for an educational intervention designed to address stigmatizing beliefs about people with mental health and addiction problems. The aim of the present study was to measure the extent to which an educational intervention – guided clinical experience in an acute mental health unit during the first year of the curriculum – decreased stigmatizing beliefs of undergraduate nurses towards those with mental health and addiction issues. In a before‐and‐after design, Corrigan's Attribution Questionnaire was used to collect data pre‐ and post‐guided clinical experience in an acute mental health unit. The intervention resulted in a significant positive change in stigmatizing attitudes for four of the nine factors tested. There was a non‐significant positive change in three factors, while two factors showed a non‐significant negative change. Using guided clinical experience as an educational intervention in the first year of an undergraduate nursing curriculum can contribute to positive change in undergraduate nurses' stigmatizing beliefs. The findings have implications for teaching of mental health content in undergraduate nursing programmes.